Vai trò của rừng ngập mặn trong quản lý đới bờ - Phước, Võ Lương Hồng; An, Đặng Trường (Vietnam Journal of Earth Sciences, 2012)
summaryThe role of mangrove forests in coastal zone managementMangrove forests are classified as the most vulnerable ecosystem among the coastal ecosystems. Mangrove forests are also dynamic systems and have direct influences on coastal erosion and accumulation processes. Mangrove forests are considered as an effective and friendly barrier for the coastal habitants against high waves, storms and especially terrible tsunamis. From a physicalviewpoint, some scientific researches as well as field measurements in some study sites in Can Gio mangrove Biosphere Reserve (Ho Chi Minh city) are made to prove the role of mangroves in soil retention and wave energy dissipation in mangrove forests. As a result, the coastal zone management in the mangrove area should be closely connected with “wisely-use” and adaptive management for mangrove forest ecosystem.